Israel-Palestine Conflict: Tracking Global Economic Responses and Fears - Ega Rusanti; Ainul Fatha Isman; Nashrullah Nashrullah; Abdurrahman Mansyur; Amina A.A Elzaanin (Shirkah: Journal of Economics and Business, 2025)
Studying the Israeli-Palestinian conflict is crucial for understanding the global economy, as it significantly influences the economic policies of various countries in anticipation of impacts and challenges. This study analyzes the global economic response and fear of the Israeli-Palestinian conflict. The research method used was descriptive qualitative with a phenomenological approach. The data source is 60 selected news articles from trusted online news platforms that present expert opinions regarding the economic impact of the Israeli-Palestinian conflict. The analysis was carried out using NVivo 12 software. The research found that the world's response and fear are focused on the energy market, particularly regarding price increases, oil and gas import and export, and concerns about a potential oil embargo. The second major issue discussed is political tensions among GCC member countries, which affect the investment climate, including money and capital markets. The conflict is also expected to slow economic growth and recovery after the COVID-19 pandemic, involving major countries, such as the United States, various Asian nations, and several European countries. This study contributes to the economic literature and international relations by offering new insights into how regional conflicts impact global economic dynamics. This provides a foundational basis for stakeholders to develop strategic economic policies in response to the conditions arising from the conflict.